Analysis of the Suitability of C-Band Radar-Based Rainfall Data with Rain Gauge Stations in the Upper Ciliwung Watershed, Indonesia - Ghinannafsi, Daffa Aliyo; Anggraheni, Evi; Rizal, Muhammad; Halim, Peter Hartono (CSID Journal of Infrastructure Development, 2026)
Accurate rainfall estimation is essential for hydrological modelling and flood risk management, particularly in mountainous watersheds where rain gauge coverage is limited. This study evaluated the performance of a calibration correction method for C-Band radar rainfall estimates in the Upper Ciliwung Watershed using data from five rain gauge stations and 100 rainfall events. Data quality was verified through outlier and consistency tests before applying a daily calibration correction factor derived from gauge observations. Radar performance was evaluated using the Nash-Sutcliffe Efficiency (NSE), Percent Bias (PBias), and Root Mean Square Error (RMSE). Before correction, radar estimates substantially overestimated rainfall, with NSE values below -500, RMSE values above 300 mm, and PBias exceeding 1000% at all stations. A uniform correction factor of 0.077 reduced systematic bias, decreasing RMSE to below 35 mm and improving NSE values, although no station achieved the satisfactory threshold (NSE > 0.5). Accuracy after correction ranged from 13.22% to 56.28%. The results demonstrate that the calibration method substantially reduced radar bias but did not achieve sufficient accuracy for direct hydrological applications. Additional correction techniques are required before C-Band radar rainfall data can be reliably integrated into hydrological models and operational flood warning systems in the Upper Ciliwung Watershed.